1973
DOI: 10.1021/ma60033a026
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis of Poly(propylene-β-d oxide) by Proton Nuclear Magnetic Resonance Spectroscopy

Abstract: Pmr Structure Analysis of Poly(propylene oxide) 459 should be the most probable of the pentads deriving from BAA triads. Similar observations can be made for every peak in the spectrum; again, the observed frequences correspond to the calculated pentad sequences with higher ethylene content. Owing to the low number of transients presently used we think that an analysis at even lower vinyl acetate content is possible; experiments on polymers containing a very small amount of each monomer are in progress.Another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The fractions obtained from the MO data are comparable with the previous results.11 Both studies have estimated the conformational stability of bond b to be in the order g+ > t > g-. This tendency can be confirmed from NMR data reported by Hirano et al 54 and Oguni et al 55 It can be concluded that, in terms of the bond conformation, the previous and present studies have reached almost the same solution. For the conformational energies, however, these two studies have given different conclusions; Abe et al have suggested that the g+ preference of the C-C bond is due to the attractive firstorder a interaction, while the present MO calculations indicate that the gauche oxygen effect arises from the attractive C-H"*0 interactions (aq, aq, and y).…”
Section: Resultssupporting
confidence: 89%
“…The fractions obtained from the MO data are comparable with the previous results.11 Both studies have estimated the conformational stability of bond b to be in the order g+ > t > g-. This tendency can be confirmed from NMR data reported by Hirano et al 54 and Oguni et al 55 It can be concluded that, in terms of the bond conformation, the previous and present studies have reached almost the same solution. For the conformational energies, however, these two studies have given different conclusions; Abe et al have suggested that the g+ preference of the C-C bond is due to the attractive firstorder a interaction, while the present MO calculations indicate that the gauche oxygen effect arises from the attractive C-H"*0 interactions (aq, aq, and y).…”
Section: Resultssupporting
confidence: 89%
“…Jedlinski used 13 C NMR spectroscopy to examine the microstructure of poly­(propylene oxide) obtained from Al­(O i Pr) 3 and Al­(O i Pr) 3 /ZnCl 2 systems and to investigate modes of epoxide ring opening. The 13 C NMR spectrum of poly­(propylene oxide) synthesized using Al­(O i Pr) 3 displayed a significant number of regioerrors . By contrast, poly­(propylene oxide) synthesized using Al­(O i Pr) 3 /ZnCl 2 had a 13 C NMR spectrum consistent with that of a regioregular (HT only) polymer.…”
Section: Stereoselective Epoxide Homopolymerizationmentioning
confidence: 95%
“…Effect of catalyst proportion upon the viscosimertic molecular weight. According to the work published by Oguni et al [38] and Ishimori et al [39] The signals of protons in the groups underlined in reaction (2) are to close to the corresponding signals from the chain, therefore hydroxyl end-groups were converted into the ester groups by reaction with trifluoroacetic anhydride. Thus, fourfold excess of (CF 3 CO) 2 O was added directly to the NMR tubes containing solution of PPO diol.…”
Section: H-nmr Studymentioning
confidence: 99%